Role of Nrf2, STAT3, and Src as Molecular Targets for Cancer Chemoprevention - Haseeb Ahsan; Salman Ul Islam; Muhammad Bilal Ahmed; Young Sup Lee (MDPI AG, 2022)
Cancer is a complex and multistage disease that affects various intracellular pathways, leading to rapid cell proliferation, angiogenesis, cell motility, and migration, supported by antiapoptotic mechanisms. Chemoprevention is a new strategy to counteract cancer; to either prevent its incidence or suppress its progression. In this strategy, chemopreventive agents target molecules involved in multiple pathways of cancer initiation and progression. Nrf2, STAT3, and Src are promising molecular candidates that could be targeted for chemoprevention. Nrf2 is involved in the expression of antioxidant and phase II metabolizing enzymes, which have direct antiproliferative action as well as indirect activities of reducing oxidative stress and eliminating carcinogens. Similarly, its cross-talk with NF-κB has great anti-inflammatory potential, which can be utilized in inflammation-induced/associated cancers. STAT3, on the other hand, is involved in multiple pathways of cancer initiation and progression. Activation, phosphorylation, dimerization, and nuclear translocation are associated with tumor cell proliferation and angiogenesis. Src, being the first oncogene to be discovered, is important due to its convergence with many upstream stimuli, its cross-talk with other potential molecular targets, such as STAT3, and its ability to modify the cell cytoskeleton, making it important in cancer invasion and metastasis. Therefore, the development of natural/synthetic molecules and/or design of a regimen that can reduce oxidative stress and inflammation in the tumor microenvironment and stop multiple cellular targets in cancer to stop its initiation or retard its progression can form newer chemopreventive agents.